Expression and functions of cellular prion proteins in immunocytes. (26th December 2019) - Zhang, Baizhuo; Shen, Pingping; Yin, Xiang; Dai, Yanyuan; Ding, Mingxuan; Cui, Li
Abstract: Prion diseases are fatal neurodegenerative processes caused by the accumulation of the pathological prion protein, PrP Sc . While pathological lesions are limited to the central nervous system (CNS), disease‐specific proteins accumulate and replicate in secondary lymphoid organs prior to neuroinvasion, and their replication there depends on the abundance of cellular prion protein (PrP C ). PrP C is expressed in both central and peripheral lymphoid tissues, and up‐ or downregulates innate and adaptive immune responses. In addition to prion diseases, PrP C is also immunologically involved in other neurological disorders and infectious diseases, including Alzheimer's disease and human immunodeficiency virus infection. Herein, we summarize the expression and functions of PrP C in various immunocytes, as well as its immunological and pathological roles in neurodegeneration and infection.